Entropy-Based Approach for Fatigue Crack Growth Rate of Dual-Phase Steel - Idris, Roslinda; Abdullah, Shahrum; Thamburaja, Prakash; Omar, Mohd. Zaidi (International Journal of Integrated Engineering, 2018)
This paper presents an entropy-based approach for the fatigue crack growth of dual-phase steel under a constant amplitude loading. According to the degradation-entropy generation theorem, the degradation coefficient can be derived from the correlations of entropy and crack propagation.Â The temperature evolutions induced for the duration of the fatigue crack growth tests on the as-received and dual-phase steel till it failed were measured to ensure their validity. The results of the present model and the calculated Paris-regime crack growth data were analysed to reach the conclusion that the temperature at the surface of a specimen during a fatigue crack growth test can be used for the assessment of fatigue crack growth by the intensity of the degradation coefficient. The predicted results showed that the present model could accurately predict the fatigue crack growth rate of dual-phase steel with a regression value (R2) of 0.9952.